Kebijakan Deviden, Investasi, Pendanaan, dan Tata Kelola Terhadap Nilai Perusahaan pada Perusahaan LQ45 di Bursa Efek Indonesia Tahun 2014 – 2017 - Mufidah Mufidah (J-MAS (Jurnal Manajemen dan Sains), 2019)
This research aimed to examine the influence of dividend policy,investment, funding and, corporate governance  to firm value  of the Company listed in indeks LQ45 in Indonesia. Firm value was proxied by Tobin’s Q (market-based financial performance). Dividend policy was measured by dividend payout ratio, investment was measured by price earning ratio and funding was measured by debt equity ratio,while Corporate governance was identified by number of audit committee. The study used 19 companies as a sample listed on Indonesian Stock Exchange in the period of 2014-2017. The sample was determined by using purposive sampling.  This study uses secondary data from financial statements of companies. Classic assumption test in this study include normality test, multicollinearity test, heterocedasticity test and autocorrelation test. Analysis of data using multiple linear regression analysis, t test, F test, and test the coefficient of determination. Analysis of data using multiple linear regression analysis with SPSS 22. The results showed only dividend policy had positive effect on firm value.